2009
DOI: 10.1186/1477-7525-7-75
|View full text |Cite
|
Sign up to set email alerts
|

Utility of WHOQOL-BREF in measuring quality of life in Sickle Cell Disease

Abstract: Background: Sickle cell disease is the commonest genetic disorder in Jamaica and most likely exerts numerous effects on quality of life (QOL) of those afflicted with it. The WHOQOL-Bref, which is a commonly utilized generic measure of quality of life, has never previously been utilized in this population. We have sought to study its utility in this disease population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 38 publications
2
38
0
3
Order By: Relevance
“…32 Importantly, the domain of physical health measured by the WHOQOL-BREF has been shown by other studies to correlate significantly with clinical variables such as haemoglobin levels and serum lactate dehydrogenase. 33 Previous studies have reported that a greater number of co-morbidities have been associated with poorer QOL, such as a study from Turkey which employed the Nottingham Health Profile to examine QOL, 34 and a German study of patients with diabetes which employed the EQ-5D tool. 35 Our findings are consistent with previously observed relationships, and with the fact that we have previously reported a greater number of co-morbidities in men from lower SES in this randomly selected sample.…”
Section: Physical Healthmentioning
confidence: 99%
“…32 Importantly, the domain of physical health measured by the WHOQOL-BREF has been shown by other studies to correlate significantly with clinical variables such as haemoglobin levels and serum lactate dehydrogenase. 33 Previous studies have reported that a greater number of co-morbidities have been associated with poorer QOL, such as a study from Turkey which employed the Nottingham Health Profile to examine QOL, 34 and a German study of patients with diabetes which employed the EQ-5D tool. 35 Our findings are consistent with previously observed relationships, and with the fact that we have previously reported a greater number of co-morbidities in men from lower SES in this randomly selected sample.…”
Section: Physical Healthmentioning
confidence: 99%
“…respecto a los puntajes por dominio obtenidos al aplicar el whoqol-bref (rango posible se encuentra entre [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], se puede observar en la Tabla 2 que este fue similar en los dominios salud física, psicológica y relaciones sociales, y sólo inferior en aproximadamente un punto, en el referido a medio ambiente. en ninguna de las dimensiones el puntaje presentó una distribución normal.…”
Section: Descripción Del Grupo En Estudiounclassified
“…Validaciones del whoqol-bref se encuentran en la literatura en adultos mayores [8][9][10][11][12] , población general 13 y con problemas de salud y otras condiciones [14][15][16][17] . en Chile, un estudio ha usado la versión oficial española de este instrumento, sin embargo, en él no se describe si fueron evaluadas las características psicométricas del instrumento y confianza para la aplicabilidad en nuestro medio 18 .…”
unclassified
“…Pain The pain can last for hours to a week or more and is typically of a throbbing nature with a tendency to move around the body. Bones are often affected and abdominal pain with tenderness is common [16,17]. SCD.…”
Section: Introductionmentioning
confidence: 99%